2021
DOI: 10.1016/j.heliyon.2021.e06533
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and antioxidant properties of cream and orange-fleshed sweet potato

Abstract: The rate of micronutrient deficiency has been on an increase since the last decade and the utilization of bio-fortified crops could help to alleviate this deficiency and food insecurity in Africa especially in Nigeria. The aim of this study was to compare the biochemical and antioxidant properties of cream-fleshed and orange-fleshed sweet potato. The varieties of OFSP used in this study were mother's delight (MDP) and king J (KJP) orange-fleshed sweet potato while the other variety was cream-fleshed sweet pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Protein content of peeled SP-based flours was higher than the unpeeled SP-based flours which is in consistent with other studies (Chikpah et al, 2020;Shaari et al, 2021). The crude protein content ranged between 5.83 and 6.28% which was low compared to that in orange fleshed (Chikpah et al, 2020) and purple fleshed (Shaari et al, 2021) sweet potato flour, but higher than that reported by other studies (Senanayake et al, 2013;Ohizua et al, 2017;Oloniyo et al, 2021). The protein content of agricultural products depends not only on varieties but also varies with environmental location (Dereje et al, 2020).…”
Section: Proximate Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…Protein content of peeled SP-based flours was higher than the unpeeled SP-based flours which is in consistent with other studies (Chikpah et al, 2020;Shaari et al, 2021). The crude protein content ranged between 5.83 and 6.28% which was low compared to that in orange fleshed (Chikpah et al, 2020) and purple fleshed (Shaari et al, 2021) sweet potato flour, but higher than that reported by other studies (Senanayake et al, 2013;Ohizua et al, 2017;Oloniyo et al, 2021). The protein content of agricultural products depends not only on varieties but also varies with environmental location (Dereje et al, 2020).…”
Section: Proximate Compositionsupporting
confidence: 89%
“…Therefore, conversion of fresh tubers into flours through appropriate techniques is quite important to preserve the bioactive compounds contained in the raw material (Khanh et al, 2018). The TPC recorded in flour samples (Table 1) ranged from 53.15 to 132.58 mgGAE/100 g, which were lower than those reported in other studies (Khanh et al, 2018;Chikpah et al, 2020;Oloniyo et al, 2021); whereas, Abong et al (2020) did not detected polyphenols in white fleshed SP from Kenya. Oke & Workneh (2013) reported that a large variation in phenolic content is observed among sweet potato varieties.…”
Section: Polyphenol and Tannin Contentmentioning
confidence: 68%
“…Particularly, Boni INTA presented a considerably high concentration (p < 0.05) with almost one order of magnitude over the Arapey genotype. The range of total carotenoid concentrations in orange-fleshed sweet potato roots found in previous studies is wide (16–1331 µg β-carotene/g dw) ( Kim et al, 2015 , Koala et al, 2013 , Oloniyo et al, 2021 , Othman et al, 2017 ). Remarkably, the content in Boni INTA was comparable to the higher values of that range.…”
Section: Resultsmentioning
confidence: 91%
“…The presence of a considerable mineral in sweet potato indicates again the nutritional benefit in the adoption of releases cultivars. Indeed, minerals are desirable in the human body for many functions such as the cellular activity of enzymes, nerve responses, muscle contraction, blood clotting [39]. The health benefits of OFSP are important to consider in its promotion amongst farmers.…”
Section: Nutritional Properties Of Different Sweet Potatoes Cultivars Selectedmentioning
confidence: 99%